Temporal and Spatial Evolution Characteristics of Extreme Climate Events in Grand Shangri-La Region from 1961 to 2019 - WU Yang; JIN Hanyu; CHENG Qingping (Renmin Zhujiang)
The Grand Shangri-La region connects the Qinghai-Tibet Plateau,the Yunnan-Guizhou Plateau,and the Hengduan Mountains and is of great geographical significance.Five rivers flow through the region,and the climate is vulnerable.Therefore,it is necessary to explore extreme climate changes and their response mechanism,so as to assess regional climate risks and achieve disaster warnings.Based on the daily temperature and precipitation data of 56 meteorological stations from 1961 to 2019,this paper analyzes changes in extreme climate indexes and their correlation with large-scale circulation index in the region by using Mann-Kendall,Sen's slope estimation,Pettitt test,and Pearson correlation analysis.The results show that:① The extreme warm index and the extreme precipitation intensity index (RX1day,R95p,R99p,and SDII) increase significantly,while the cold index (CSDI、FD、ID、TN10p、TX10p) and the number of continuous humid days decrease greatly.In terms of different seasons,the warming amplitude of most of the extreme temperature indexes in winter is higher than that in summer,and the precipitation intensity increases gradually in summer and autumn but decreases slightly in winter.② Spatially,the diurnal temperature range in the north of the Qinghai-Tibet Plateau is higher than that in the south,and the frequency of extremely high-temperature rises,with the high temperature appearing mostly in arid valleys in the south and east of the Qinghai-Tibet Plateau.The precipitation intensity is high in the south and west of the Hengduan Mountains,and persistent precipitation is strong in the Yalong River basin and the upper reaches of the Jinsha River in the north.③ Extreme climate indexes and south China sea summer monsoon index (SCSMI) are significantly correlated in the same year.In addition,there is a one-year response lag between the extreme precipitation index and Arctic oscillation (AO),North Atlantic oscillation (NAO),and Pacific decadal oscillation (PDO).The above analysis shows that the Grand Shangri-La region generally shows warming and humid climate characteristics.The frequency of heavy precipitation in flood season and warm winter events increases and is closely related to large-scale circulation.